Preguntas Sobre Cáncer (Questions About Cancer): Analysis of Spanish Inquiries to the National Cancer Institute’s Cancer Information Service - Eduardo J. Santiago-Rodríguez; Diane Ng; Beth Slotman; Robin C. Vanderpool (Journal of Cancer Education, 2026)

Cancer, HIV, and stigma: a portfolio analysis of grants funded by the National Cancer Institute - Irina A. Iles; Anna Gaysynsky; Rebecca A. Ferrer; Robin C. Vanderpool (Cancer Causes & Control, 2025)

Building capacity for community outreach and engagement activities across the translational research continuum at NCI Cancer Centers - Robin C. Vanderpool; Abigail Muro (Cancer Causes & Control, 2024)

Childhood Cancer Information-Seeking: Findings from the National Cancer Institute’s Cancer Information Service - Robin C. Vanderpool; Grace Huang; Ashley Wilson; Rebecca Gordon; Michelle A. Mollica; Candace Deaton Maynard (Journal of Cancer Education, 2023)

Communication research at the National Cancer Institute, 2013–2019: a grant portfolio analysis - Anna Gaysynsky; Camella J. Rising; Neha Trivedi; Kelly D. Blake; Wen-Ying Sylvia Chou; April Oh; Robin C. Vanderpool (Cancer Causes & Control, 2021)

A Brief Educational Intervention Enhances Basic Cancer Literacy Among Kentucky Middle and High School Students - Lauren Hudson; Kerrigan M. Samons; Haley E. Dicken; Chris Prichard; L. Todd Weiss; Jean Edward; Robin C. Vanderpool; Nathan L. Vanderford (Journal of Cancer Education, 2021)
Kentucky experiences the highest overall cancer incidence and mortality rates in the USA with the greatest burden in the eastern, Appalachian region of the state. Cancer disparities in Kentucky are driven in part by poor health behaviors, poverty, lack of health care access, low education levels, and low health literacy. Individuals with inadequate health literacy are less likely to participate in preventive measures such as obtaining screenings and making healthy lifestyle choices, thus increasing their chances of developing and dying from cancer. By increasing cancer literacy among youth and adults, it may be possible to decrease cancer disparities across Kentucky. This study aimed to establish connections with middle and high schools in Kentucky that would facilitate pilot implementation of a brief cancer education intervention and assessment of cancer health literacy among these student populations. A baseline pretest cancer literacy survey consisting of 10 items was given to 349 participants, followed by the delivery of a cancer education presentation. Immediately following the presentation, participants were given a posttest with identical items to the pretest. Participants were primarily Caucasian (89.4%), female (68.7%), and in 10th through 12th grade (80.5%). Significant ( p < 0.0001) increases in both average and median percent of correctly marked items were observed between the pretest and posttest (average, pretest = 56% versus posttest = 85%; median, pretest = 60% versus posttest = 90%). The scores for all individual items increased after the brief intervention. The results demonstrated a significant increase in cancer literacy levels immediately after the pilot educational intervention. We suggest that it may be possible to improve cancer literacy rates in Kentucky by integrating cancer education into middle and high school science and/or health education curricula. This could ultimately drive changes in behaviors that may help lower cancer incidence and mortality rates. Plans for future interventional studies measuring long-term cancer knowledge retention and resultant behavioral changes among middle and high school students as well as the feasibility of integrating cancer education into middle and high school curricula are also discussed.

A Hope-Based Intervention to Address Disrupted Goal Pursuits and Quality of Life Among Young Adult Cancer Survivors - Carla J. Berg; Robin C. Vanderpool; Betelihem Getachew; Jackelyn B. Payne; Meghan F. Johnson; Yasmeni Sandridge; Jennifer Bierhoff; Lana Le; Rakiyah Johnson; Amber Weber; Akilah Patterson; Sarah Dorvil; et al. (Journal of Cancer Education, 2020)

Cancer–work management during active treatment: towards a conceptual framework - Jennifer E. Swanberg; Robin C. Vanderpool; J. Kathleen Tracy (Cancer Causes & Control, 2020)

Patient-Provider Communication: Experiences of Low-Wage-Earning Breast Cancer Survivors in Managing Cancer and Work - Helen M. Nichols; Jennifer E. Swanberg; Robin C. Vanderpool (Journal of Cancer Education, 2019)

Evaluating centralized technical assistance as an implementation strategy to improve cancer prevention and control - Sarah Moreland-Russell; Prajakta Adsul; Seif Nasir; Maria E. Fernandez; Timothy J. Walker; Heather M. Brandt; Robin C. Vanderpool; Meagan Pilar; Paula Cuccaro; Wynne E. Norton; Cynthia A. Vinson; David A. Chambers; et al. (Cancer Causes & Control, 2018)

Cancer and Employment Issues: Perspectives from Cancer Patient Navigators - Robin C. Vanderpool; Helen Nichols; Elizabeth F. Hoffler; Jennifer E. Swanberg (Journal of Cancer Education, 2017)

Providers’ Perspectives of Survivorship Care for Young Adult Survivors of Childhood Cancer - Carla Berg; Erin Stratton; Natia Esiashvili; Ann Mertens; Robin C. Vanderpool (Journal of Cancer Education, 2016)

Perceptions of Cancer Controllability and Cancer Risk Knowledge: The Moderating Role of Race, Ethnicity, and Acculturation - A. Susana Ramírez; Lila J. Finney Rutten; April Oh; Bryan Leyva Vengoechea; Richard P. Moser; Robin C. Vanderpool; Bradford W. Hesse (Journal of Cancer Education, 2013)

Cancer information-seeking experiences: The implications of Hispanic ethnicity and Spanish language - Robin C. Vanderpool; Julie Kornfeld; Lila Finney Rutten; Linda Squiers (Journal of Cancer Education, 2009)